Gliding movements in Myxococcus xanthus. - Spormann, A M (1995)
Prokaryotic gliding motility is described as the movement of a cell on a solid surface in the direction of the cell's long axis, but its mechanics are unknown. To investigate the basis of gliding, movements of individual Myxococcus xanthus cells were monitored by employing a video microscopy method by which displacements as small as 0.03 micron could be detected and speeds as low as 1 micron/min could be resolved. Single cells were observed to glide with speeds varying between 1 and 20 microns/min. We found that speed variation was due to differences in distance between the moving cell and the nearest cell. Cells separated by less than one cell diameter (0.5 micron) moved with an average speed of 5.0 micron/min, whereas cells separated by more than 0.5 micron glided with an average speed of 3.8 microns/min. The power to glide was found to be carried separately at both ends of a cell.